Probabilistic estimation of the large heel due to broaching associated with surf-riding for a ship in short-crested irregular waves and its experimental validation - Matsubara, Kazuma; Umeda, Naoya; Matsuda, Akihiko (Ocean engineering, 2023)
The International Maritime Organization started using a numerical simulation to quantify the probability of a ship's stability failure as a direct stability assessment for broaching associated with surf-riding. Some of the authors proposed a critical wave method to estimate such probability, and its numerical verification and experimental validation in long-crested irregular stern-quartering waves were already published. The remaining issue is numerically verifying and experimentally validating the methodology applied to short-crested irregular stern-quartering waves. The work described in this paper is an attempt to resolve this remaining issue by executing numerical simulation and a free-running model experiment in both short-crested and long-crested irregular waves. The subject ship used in this work is an ocean research ship similar to the one lost in actual stern-quartering waves with higher speed, which was used in our previous study in regular waves. The experimental results indicate that the direct counting in the numerical simulation shows stochastically sufficient agreement with the model experiment, and the critical wave method provides reasonably conservative estimates even in short-crested irregular waves. •Broaching associated with surf-riding was realized in short-crested irregular waves at a model scale.•Probability of large-heels due to broaching is estimated using numerical simulations and model experiments.•Experimental validation of direct counting numerical simulation is reported.•Critical wave method provides a conservative estimate of broaching probability.